Research and application of medicines for treating liver fibrosis: current status and prospects - Chen, Shiqi; Wu, Zhu; Zhang, Jing; Lin, Yuxin; Xie, Jiaqi; Yin, Dehui; Zhu, Ye (Frontiers in Pharmacology, 2025)
Ethnopharmacological RelevanceLiver fibrosis is a common pathological consequence of multiple chronic liver diseases, making its pharmacological management a key area of medical research. Diverse classes of therapeutic agents offer distinct advantages and limitations. Notably, combination therapy has emerged as a prominent focus of contemporary investigation due to its potential to enhance treatment outcomes.Materials and MethodsAs of 1 February 2025, a comprehensive literature search was conducted using PubMed and Web of Science, employing keywords related to liver fibrosis and its treatment. In accordance with ConPhyMP guidelines, one author assessed the quality of studies involving botanical drug metabolites.ResultsThis review synthesizes findings from 111 research articles, offering an overview of two primary classes of therapeutic agents and their integration with emerging technologies-namely mesenchymal stem cell-derived exosomes and nanoparticles. On one side, it discusses biomedicine-related therapies, including conventional biomedicine medicines, repurposed drugs, and investigational compounds. On the other, it addresses botanical-based treatments, encompassing traditional Chinese medicine (TCM) formulas and botanical drug metabolites. Both categories have shown promising therapeutic efficacy in clinical and preclinical settings.ConclusionThis review provides a comprehensive and detailed overview of pharmacological strategies for the treatment of liver fibrosis, shows the application and research status of different types of medicines, and provides a comprehensive perspective for current research directions. It points out the limitations of existing research and suggests that the clinical research of various medicines and combination therapies should be strengthened in the future, and the liver fibrosis model should be optimized to promote clinical transformation, which provides an important reference for future research directions.